Analisis Strategi Komunikasi Pemasaran Pada PT.PT. Bank Aceh Melalui Pendekatan Teori AIDA - Cut Devi maulidasari; Yusnaidi Yusnaidi (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
Abstract                                                                     This research was conducted to analyze and illustrates the used of AIDA model  in  marketing communication or an advertisement to engages and persuades the consumers in purchasing decision or choosing the brand. The descriptive analysis research methodology was used as the method to implement the research through qualititave reseach .   It will describes the marketing communication strategy used by PT. Bank Aceh to promote their product to the consumers in Aceh Province. AIDA theoritical approach which was introduced by Wilbur Schramm, has been used to analyze the marketing programs and the effectiveness of programs to target the consumers. The respondents are the consumers of PT. Bank Aceh which were considered had better understanding of the marketing programs and the impacts to their choice when they have to make decision of purchasing banking products and facilities. The result shows that the marketing communication strategies which have been implemented by PT. Bank Aceh have been considered as the effective strategy to approach new customers and to maintain customer retention. However, it needs improvement in term of media and the dilivered messages to adapt to the latest customers lifestyle.  Keywords : AIDA Model, Marketing Communication, Promotion